Sales Pricing Strategy of Karak Kaliang Talua and Roti Kariang Household Industries by Determined Prices of Existing Costs - Nilda Tri Putri; M Alif Arrahman; Adisty Luthfiah; Muhammad Erlangga Adi Nugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
This article aims to determine how product selling prices were determined at MSMEs Karak Kaliang Talua RF. Data collection used the observation method by conducting interviews with the owner, asking several questions related to his business, and documenting the results of the observation visit. Based on the visit results, this business had a reasonably small target market by marketing only entrusting products to traders in traditional markets. The owner expects a profit of IDR 5,000/0.25kg for each product, namely Karak Kaliang Talua and Roti Kariang. The owner of Karak Kaliang Talua RF sets prices based only on estimated cost prices and profit expectations. After processing the data from the interview results, it was found that there was a discrepancy between the selling price set by the owner and the profit expectations.